NEW ECOLOGICAL THINKING DEVELOPMENT AS A WAY TO ENVIRONMENTAL PRESERVATION - Kuchai, Tetiana; Honcharuk, Vitaly; Rokosovyk, Natalia; Zorochkina, Tetiana (Mountain School of Ukrainian Carpaty, 2022)
The article focuses on the actual global problem of ecological education and the basic principles of preservation of natural environment. The development of aims and tasks of ecological training of a teacher, which has to understand the importance of ecological education in accordance with modern approaches, which are acknowledged in international pedagogical practice. It is highlighted that the qualification of a teacher of any occupation should guarantee the professional readiness to realizing the tasks of ecological education. Special attention is paid to ecological education which is to supply a young generation with scientific knowledge about intercommunication of nature and society. It also should help young people to understand the many-sided value of nature for the society on the whole and everybody in particular, and to make a requirement in socializing with nature, to teach them the standards of correct conduct in the process of co-operating with the nature, to develop aspiration and ability to actively participate in preserving the environment. Keywords: ecological education, training of teacher, education of young people, professionalism, environment.